Physiotherapy and ecosystem services: improving the health of our patients, the population, and the environment. (1st February 2023) - Stanhope, Jessica; Maric, Filip; Rothmore, Paul; Weinstein, Philip
ABSTRACT: Introduction: The relevance of ecosystems to physiotherapy has traditionally been overlooked, despite its potential for health impacts relevant to conditions often managed by physiotherapists. Purpose: The purpose of this article is to introduce the concept of ecosystem services to physiotherapists, and to discuss how understanding ecosystem services may improve patient care, and population and planetary health. Discussion and Conclusion: Physiotherapists with an understanding of ecosystem services may improve patient care by value-adding to management through patient education, empathy, advocacy, and broader population health approaches. Physiotherapists are also well placed to promote the conservation and restoration of ecosystem through participation, advocacy, and the development of public health measures, to the benefit of global sustainability and population health. Further research is required into how physiotherapists currently use nature-based interventions, and the barriers and enablers to their use. To be adequately prepared to meet the challenges that climate change and environmental degradation pose to patient care, population health and health systems, both current and future physiotherapists need to take a broader view of their practice. By including consideration of the potential role of the environment and green space exposure in particular on their patient's health, physiotherapists can ultimately contribute more to population and planetary health.